2020
DOI: 10.1155/2020/4918453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aqueous and Methanolic Extracts of Stem Bark of Alstonia boonei De Wild. (Apocynaceae) on Dextran Sodium Sulfate‐Induced Ulcerative Colitis in Wistar Rats

Abstract: Among the most exploited species in Cameroon, Alstonia boonei is widely used in African medicine for the relief of several pathologies including gastrointestinal disorders. This study was conducted in order to assess the effects of aqueous and methanol stem-bark extracts of Alstonia boonei on DSS- (dextran sodium sulfate-) induced intestinal colitis and to determine its antioxidant potential. The classes of secondary metabolites present in these extracts were determined by chemical screening. The production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…The animals received a composed feed and drinking water ad libitum . With reference to the work of Adjouzem et al [ 24 ], the experimental procedures have been approved by the local ethics committee and are in accordance with the guidelines for the study of pain in awake animals, published by the NIH Publication No. 85-23 “Principles of Animal Protection,” Laboratory Study of Pain, Ministry of Scientific Research and Technology, which adopted the European Union Guidelines on Animal Care and Experimentation (EWC 86/609).…”
Section: Methodsmentioning
confidence: 99%
“…The animals received a composed feed and drinking water ad libitum . With reference to the work of Adjouzem et al [ 24 ], the experimental procedures have been approved by the local ethics committee and are in accordance with the guidelines for the study of pain in awake animals, published by the NIH Publication No. 85-23 “Principles of Animal Protection,” Laboratory Study of Pain, Ministry of Scientific Research and Technology, which adopted the European Union Guidelines on Animal Care and Experimentation (EWC 86/609).…”
Section: Methodsmentioning
confidence: 99%
“…The entire colon from the ileocolic junction to the anus was quickly removed, opened longitudinally along the mesenteric fixation line, then washed with saline in a reservoir of ice water and dried with filter paper; then, the total length of the two points was measured [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The same colon removed, washed, and dried was photographed using a Canon camera (Cyber-shot, 7.2 megapixels, China); then, the samples from this colon were fixed in 10% formalin buffered with PBS. The sections were made in pieces of 5 μ m each; then, staining was done with hematoxylin-eosin (H&E) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The works of Awodele et al [12] showed that the aqueous extract of the stem bark of Bridelia ferruginea Benth did not cause mortality in rodents administered orally at various doses of 250 mg/kg to 4000 mg/kg. Regarding Alstonia boonei De Wild, studies carried out with extracts show that this plant species has no toxic effect at the doses tested in the models used [13][14][15]. It clearly appears that the toxicological studies on in vitro and in vivo models are very important before the use of medicinal plants.…”
Section: Introductionmentioning
confidence: 99%